2022
DOI: 10.1097/j.jcrs.0000000000000866
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the vitreolenticular interface with intraoperative OCT

Abstract: Age is a risk factor for AVD. Posterior capsulorhexis does not cause and might even prevent postoperative ocular complications in the posterior segment to a certain degree.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 26 publications
1
19
0
Order By: Relevance
“…In addition, AVD seems to be more likely to occur in men and in older patients. This is in line with the point made by Vael et al 8 iOCT showed that the AVD mostly originated from the periphery of the lens capsule and gradually progressed to the center, and a crescent-shaped cavity was formed (Figure 1). In cases of AVD, detachment in the lower part of the eye is the most common, which may be because the transparent corneal incision is often located in the upper part of the eye.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In addition, AVD seems to be more likely to occur in men and in older patients. This is in line with the point made by Vael et al 8 iOCT showed that the AVD mostly originated from the periphery of the lens capsule and gradually progressed to the center, and a crescent-shaped cavity was formed (Figure 1). In cases of AVD, detachment in the lower part of the eye is the most common, which may be because the transparent corneal incision is often located in the upper part of the eye.…”
Section: Discussionsupporting
confidence: 91%
“…11 Anisimova et al and Vael et al reported that the intraoperative incidence of AVD was 75.0% and 63.0%, respectively. 7,8 There were considerable differences between the studies. To the authors' knowledge, there are no available reports on the effects of phacoemulsification cataract surgery on AVD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When studying a large series of adult eyes with the intraoperative OCT, we evaluated the incidence of AVD as a function of age. 12 We found an incidence of AVD of 65%. We do realize the bias during cataract surgery since the water column of the phako machine or the use of ophthalmic viscosurgical devices (OVD) may be responsible for hydro/visco separation of the posterior and the anterior hyaloid during the different surgical steps of the BIL surgical technique and might have facilitated or completed AVD.…”
mentioning
confidence: 60%
“…In the presence of an anterior vitreous detachment (AVD), it is more correct to speak about the anterior interface or the retro lenticular space. When studying a large series of adult eyes with the intraoperative OCT, we evaluated the incidence of AVD as a function of age 12. We found an incidence of AVD of 65%.…”
mentioning
confidence: 99%